Dispositions toward Critical Thinking in Portuguese Undergraduate Students - Eva Morais, José Lopes, Helena Silva, Caroline Dominguez, Rita Payan-Carreira, Cristina Imaginário, Maria José Santos (Educational Process: International Journal)
Background/purpose – The study aimed to identify differences in the level of critical thinking dispositions of undergraduate students in Portugal according to their sociodemographic (gender, age) and academic (study field) characteristics.